Holland at its Highest; Historical continuity and town development (Contributions to the KNOB-Symposium Holland at its Highest): Onroerend goed - erfgoed (Bulletin KNOB, 1990)
For some time now the Royal Antiquarian Society of the Netherlands follows with great concern the large-scales urban renewal projects as these are carried out in numerous Dutch towns. These projects are a serious threat to the charm and intimacy of our historical inner towns and their surroundings. Quite often urban renewal degenerates into an instrument of municipal prestige. In pursuance of this problem the Section Architecture and Town-planning of the Royal Antiquarian Society of the Netherlands organized the symposium 'Holland at its highest; Historical continuity and town development'.The invited orators represented several disciplines. Critic of architecture Max van Rooy (see: Max J.M. van Rooy, ‘Holland at its Highest’ in this number) made a comparison with the 19th century fin-du- siècle. The 'pursuit of credit balance', controlled by the 'pursuit of the top location' still determines Dutch architecture and town-planning. Only public policy can make the 'cultural component' part of the urban context again.Also immovables-developer A. Kuyvenhoven mentioned this public policy as extremely important at the economical revitalization of urban areas. One has to consider many aspects like the market of immovables, urban economy and urban context. Toplocations do not come into being 'just like that'. To reassure a responsible town-planning as well as a socially acceptable solution the municipality must bring common interests into line with the individual wishes of the future user of a building.Town-planning consultant H.A.F. Smook described a serious lack of architectural creativeness in and close to the historical inner part of town. Are there still other forms than high-rise blocks? The historical centre, having of old only a restricted number of economical functions, one cannot let functional or economical continuity have priority over historical continuity. To prevent destruction of the inner part of town's historical quality functions should be adapted to the extant urban structure instead. Quite often the town-planner stresses architectural form rather than a good urban structure. Absolutely wrong! The town in her entirety and not the separate building must be spectacular.To think and to speak with marketing-terms of project development surely is dangerous to quality. But why stick to old values stated professor Architecture and Town-planning Tj. Dijkstra. To reject new cultural impulses in the form of high-rise blocks close to the historical inner part of town cannot but lead to a 'mediocre quality-level'. Rather than arguing about terms of measure and scale it is necessary to analyse an area's characteristics in relation to the surrounding parts of town carefully. The municipality must watch over this carefulness at the plan's execution.According to protector of monuments C.J. van Haaften is the 'small-scaled process or urban renewal' the most important characteristic of the historical inner part of town. Preservation of this process demands an integration of the protection of monuments into the field of area planning. The protection of monuments has to handle a sort of classification and selection aiming at the forefront both and historical developments behind that facade. The municipality can direct area planning by means of analysis of this material.Government-planner S. Buys stated that town development with respect for the past must be directed to the preservation of commercial and administrative functions primarily. The continuity of the urban structure and separate buildings are of less importance; without economical prosperity a historical inner part of town changes into an 'open-air museum'. One of the main conclusions of this symposium is that 'true' architecture and town-planning arise from a coherence of factors and several disciplines. The separate monument belongs to an urban ensemble. On the other hand town-planner and municipality have to accept the circumstance of the historically grown inner part of town. A one-sided, mainly technical approach cannot be but too confined. The architect or town-planner with respect for the social and urban context will deliver a design as various as the historically grown town herself and might even use historical connotations. The town is there. The new has to come into being not in tension with but in dialogue with the extant. And the government is there for administration and delegation.